Educação, Cinema e Linguagem cinematográfica: Entrecruzamentos para uma metodologia de leitura filmica crítica na formaçao inicial de professores de Artes Visuais - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The purpose of this thesis is the development of an alternative of critical filmic reading for the formation of Visual Arts teachers. The question that guides the problem of this study is expressed through the following question: What is the alternative of critical filmic reading for the initial formation of teachers of Visual Arts that combines Content and Form mediated by the knowledge of the cinematographic language and that aims at human-cultural and social criticism? The general objective is to construct a methodological alternative of critical filmic reading from the cinematic reading, overcoming the fragmentation between form and content, contributing to the construction of knowledge in the initial formation of Visual Arts teachers, aiming at human, artistic-cultural and social criticism development. From the formulation of the general objective, the specific objectives listed are: Endorsing Cinema, Education and Culture in the critical epistemological perspective; Providing methodological practices of Filmic Reading mediated by the cinematographic language combining form and content in a critical perspective and Presenting a possible pedagogical- methodological alternative for Filmic Reading in the initial formation of Visual Arts teacher, combining content and form mediated by the cinematographic language. The theoretical reference is composed mainly by the authors: Adorno (1995, 2010); Adorno and Horkheimer (1986, 2014); Almeida (2016); Andrew (2002); Barbosa (1990); Benjamin (1985, 2011, 2012, 2013); Berger (1999); Bernadet (1985); Bordwell and Thompson (2013); Buoro (2003); Contreras (2002); Duarte (2009); Fernão (2012); Freire (1996); Garcia (1999); Martin (2003); Metz (2014); Mitry (1978); Reali (2007); Rüdiger (2004); Xavier (2005); among others. The research methodology is based on a qualitative approach, in the research-action modality with a focus on the dialectical historical method based on the Critical Theory. The instruments of data collection are questionnaires, seminars, filmic sessions, filmic analysis works with the undergraduate students of the 1st / 2nd year of 2016/2017 from the Visual Arts Degree Course at State University of Ponta Grossa UEPG / PR. Data analysis was performed using the Bardin Content Analysis (2009). Three (3) main guiding categories and 13 (thirteen) subcategories of analysis were raised and related with the objectives proposed in the research. The results demonstrate that with more autonomy, the teacher / spectator reaches the "competence to see" through critical filmic reading, from the knowledge inferred about Cinema, leaving aside the spontaneous reading. The undergraduate students recognize the importance of Cinema in Education, in the most significant context, by means of subsidies of the methodological alternative of filmic reading in a critical, formative, democratic and emancipatory perspective, in the formation of teachers in Visual Arts.
Keywords: Cinema; Leitura Fílmica; Formação de Professores de Artes Visuais; Educação; Cinema; Filmic Reading; Visual Arts Teacher Formation; Education; CNPQ::CIENCIAS HUMANAS::EDUCACAO